High-risk HPV prevalence and genotype distribution among women in Liaocheng, Shandong Province, China from 2016 to 2022 - Zheng, Li-li; Chen, Shuang-feng; Yang, Fei; Wang, Wei-hua; Xu, Cong; Zheng, Li-yuan (Frontiers in Public Health, 2023)
Human papilloma virus (HPV) infection and its associated disease are major problems affecting millions of individuals around the world. The distribution of HPV genotypes is specific to different areas and different populations. Therefore, understanding the prevalence and genotype distribution of HPV in different populations in different geographical regions is essential to optimize HPV vaccination strategies and to maximize vaccine effects. In this study, 34,076 patients from January 2016 to July 2022 were retrospectively analyzed at Liaocheng People's Hospital. Of these, 3963 patients were high-risk HPV positive and the infection rate was 22.13%. The top ten genotypes were as follows in descending order: HPV16, HPV52, HPV58, HPV53, HPV39, HPV59, HPV66, HPV51, HPV18, and HPV56 and the least frequent genotypes were, in order, HPV 26, HPV45, and HPV82. The HPV16 positive infection rate was 25.37% and was reduced with the increase in the number of individuals who had undergone HPV screening. The HPV52 infection rate increased with increasing numbers of individuals undergoing HPV screening, and then remained unchanged. The proportion of 20–29-year-olds among all positive patients began to decrease since the vaccine was available in 2018. The 30–39-year-old group accounted for the highest percentage of positive patients, and the 50–59-year-old group of HPV-positive patients with cervical cancer accounted for most infections. This study confirmed that HPV16, HPV52, HPV 58, and HPV53 is widely distributed in this population and the total HR-HPV infection rate remains high in this region. Our findings indicate that prevention of HPV infection in this region still faces important challenges.